Blockchain Enabled Track-and-Trace Framework for Covid-19 Immunity Certificate - Khan, D. (Institute of Electrical and Electronics Engineers Inc., 2022)
The outbreak of Coronavirus/COVID-19 pandemic is no doubt the greatest worldwide challenge at this point of time. After its discovery in China in late 2019, the virus spreads fiercely through various social transmissions, causing more than 60 million confirmed cases and close to 1.9 million deaths by early 2021. On 11th March 2020, the WHO went on to declare the onset of COVID-19 pandemic. To lessen societal pressure and restore normalcy, many countries committed to vaccination have introduced the COVID-19 immunity passports, certificates, or licenses, collectively called the COVID-19 immunity certificate. This is to legally certify that the certificate bearer has been vaccinated and is immune to COVID-19. However, there exists several practical and legal obstacles to efficiently track/trace the certificates. Matter of fact, this kind of certificate is to impose restrictions on who can and who cannot participate in an official social activity. This has regrettably promoted the fabrication of the certificate and is casting doubt on the vaccination integrity. In this paper, we thus propose a novel blockchain-based system for establishing trust on the certificate bearer and to eradicate vaccination immunity certificate fraud. Our proposed system is aimed to address the issues in trackability, and traceability of the data embedded in the immunity certificate. This is to uphold the trust on the certificate bearer/holder that all necessary precautions pertaining to COVID-19 vaccination have been legally obeyed and complied with. The system can track the origin of the COVID-19 immunity certificate and monitor the vaccines process flow at each step of its manufacturing and its associated chain of distribution. Â© 2022 IEEE.